Improving paranasal sinus computed tomography reporting prior to functional endoscopic sinus surgery – an ENT-UK panel perspective. Issue 10 (24th October 2016) - Mistry, S G; Strachan, D R; Loney, E L
Abstract: Background: Functional endoscopic sinus surgery is recognised to have a significant complication profile (e.g. blindness, cerebrospinal fluid leak and intracranial sepsis). Pre-operative computed tomography imaging is considered mandatory for surgical planning to reduce intra-operative risk. A radiological report is the 'gold standard' in image interpretation; however, because of a lack of otolaryngological or radiological guidance, its contents may be variable. By surveying practising otolaryngologists, this study aimed to provide some guidance which may be used by radiologists to produce more surgically relevant radiological reports. Method: A prospective questionnaire was distributed to the ENT-UK panel. Results: A total of 117 consultant members of the panel completed the survey. Twenty-nine per cent indicated that they were uncomfortable interpreting all areas of the computed tomography scan. Greatest importance was given to areas including the ethmoid roof (dehiscence, asymmetry and angle), lamina papyracea (dehiscence) and sphenoid sinus (carotid canal dehiscence and optic nerve relationships). Conclusion: Functional endoscopic sinus surgery is commonly performed by non-subspecialist rhinologists. The information obtained from this study can be used by radiologists to improve report relevance, particularly for the generalist ENT surgeon. This contributes to improving patient safety and helps avoid medicolegal litigation when complications arise.